Muscular strength, fitness and anthropometry in elite junior basketball players - Drinkwater, E. J. (2006)
Basketball is a sport with many complex demands that require a combination of fitness, skills, team tactics and strategies, and motivational aspects. However key areas that are likely to play an important role in a basketball player's success are muscular strength, fitness and body size. Methods of evaluating and developing these characteristics have been extensively tested in controlled research settings, but there is a dearth of research exploring the value of, and methods of improving, muscular strength, fitness and body size of basketball players within the demanding schedule of an elite junior development program. These were therefore explored in this thesis.